(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present investigation is on linear analytical study of thermohaline convective instability in micropolar ferrofluid using perturbation technique. The fluid layer is heated from below and salted from above. The theory of linear stability is used to reduce the non-linear effects on governing equations and normal mode analysis is taken to study. The critical magnetic thermal Rayleigh number NSC is obtained for sufficient large value of M1 and an oscillatory instability is determined. The parameters and are analyzed for stabilizing behavior and, and M3 give the destabilizing behavior. The results are depicted graphically.